Parental satisfaction and associated factors towards neonatal intensive care unit services at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Mohammed Seid Ali; Enyew Getaneh Mekonen; Belayneh Shetie Workneh (Elsevier, 2021)
Introduction: Satisfaction of parents is an effective parameter in improving neonatal care quality. Parent satisfaction towards the care of neonates from birth up to 28 days is an integral part of the reduction of neonatal mortality worldwide. Measuring the satisfaction of parents is one of the strategies for the management of hospitals and quality assurance as well as accreditation process in many countries. Therefore, this study was intended to assess parental satisfaction and its associated factors towards neonatal intensive care unit services, Northwest Ethiopia. Method: An institutional-based cross-sectional study was conducted in December 2020 among parents of the hospitalized neonate in the university of Gondar Comprehensive Specialized Hospital. A systematic random sampling technique was used to select 317 study participants. Data were collected by using an interviewer-administered structured questionnaire. Then the collected data were entered and cleaned using Epi data version 3.1 and then it was exported & analyzed using SPSS version 20. To determine the association between dependent and independent variables, bivariable and multivariable logistic regressions were computed. Statistical significance was declared at a p-value < 0.05 and the strength of association were determined using crude and adjusted odds ratio with a 95% CI. Result: The overall prevalence of parental satisfaction of neonatal care was 50.0%. Respondents age (AOR = 0.34, 95% CI = (0.19-0.65)), respondent's relationship with the neonate (AOR = 2.89, 95%CI= (1.20-6.98)), and length of stay (AOR = 2.42, 95%CI= (1.39-4.1.8)) were significantly associated with parental satisfaction of neonatal care. Conclusion: Half of the parents were satisfied with their neonatal care at the University of Gondar Comprehensive Specialized Hospital. Age group of below 25 years, being a mother and staying in the hospital for greater than or equal to four days increased the odds of parental dissatisfaction of neonatal care. It is better to provide timely neonatal care services and provide continuous training for health caregivers to improve parental satisfaction towards their neonatal care.